A Retrospective View of the Heisei Economy. (2nd January 2018) - Komine, Takao
Abstract : The Nakasone Yasuhiro Peace Institute (formerly Institute for International Policy Studies) marks its 30th anniversary this year in June 2018. The three decades that the Institute has existed coincide almost perfectly with the length of the Heisei period, as the fact that this is Heisei year 30 indicates. Therefore, in the present article, "Heisei economy" will be the term used in this review of developments in the Japanese economy over the past three decades.